Sharing Collections and Sharing Stories: The Importance of Archaeological Ethnography in Archaeologist–Collector Collaborations. Issue 1 (February 2022) - Mills, Nikki S.
Abstract: As archaeology has evolved, partnerships between private collectors and archaeologists have ebbed and flowed. This article contributes to a growing body of work dedicated to recognizing the contributions of the collecting community, with a focus on maintaining reciprocal models for long-term collaborations. This research article argues that for these collaborative efforts to progress, archaeologists must operate through an archaeological ethnographic lens that fosters work in partnership and generative dialogues. Utilizing ethics from the Society for American Archaeology's "Statement on Responsible and Responsive Stewards of the Past" (Society for American Archaeology 2018), an undergraduate student and private collector partnered to retroactively document an artifact collection collected over 60 years in Colorado's San Luis Valley. This article is distinct, however, in that it centers the research methods, offering a pragmatic example of utilizing an archaeological ethnographic framework alongside collaborative inquiry and oral history methodologies. The partnership cultivated within the research team opened a new line of inquiry into the collector's past collaborations with professionals, revealing a variety of informative and illuminating stories. As the academic discourse widens, incorporating such stories into the canon will improve collaborations and foster networks of partners to create sustainable long-term collaborations that ultimately lead to greater understanding of and care for the material past.